Finite element analysis of residual stress and warpage in a 3D printed semi-crystalline polymer: Effect of ambient temperature and nozzle speed - Samy, Anto Antony; Golbang, Atefeh; Harkin-Jones, Eileen; Archer, Edward; Tormey, David; McIlhagger, Alistair (Journal of manufacturing processes, 2021)
The printing conditions in Fused Deposition Modelling (FDM) affect the amount of induced residual stresses within the printed part and its dimensional accuracy. Among the thermoplastic feedstock for FDM, semi-crystalline polymers are more prone to part distortion due to crystallisation. Therefore, this study aims to numerically investigate the behaviour of semi-crystalline polymer under various FDM printing conditions (namely print speed and ambient temperature) and the resultant residual stress and warpage in the printed parts. For this, the coefficient of thermal expansion (CTE) and the thermo-mechanical properties of the polymer under study (polypropylene), and the crystallisation kinetics are coupled with the evolving temperature and time during printing. The values of residual stress and warpage are calculated and compared for the bottom and top layers of the samples. From the results, it was observed that increasing the nozzle speed from 30 mm/s to 60 mm/s resulted in the bottom and top layers exhibiting a 15% and 13% decrease in residual stress, respectively. Similarly, a drop in warpage (~30%) was observed for both layers. The reduction in residual stress and warpage with increased printing speed is attributed to the improved heat transfer between the deposited roads and the reduced cooling rate. Increasing the ambient temperature from 25 °C to 75 °C resulted in a 2% and 3% decrease in residual stress in the bottom and top layers, respectively. In terms of warpage, an insignificant increase (~1%) was observed in both top and bottom layers. This is explained by the counter effects of reduced thermal gradients (i.e., lower cooling rate) and increased crystallisation on the overall amount of residual stress and warpage. 3D scanning of experimentally printed samples was used for verification of the simulation results, and good agreement between these is reported.